1996
DOI: 10.1152/ajpheart.1996.271.3.h1186
|View full text |Cite
|
Sign up to set email alerts
|

Differences between cytokine effects in the microcirculation of the rat

Abstract: We studied by in vivo microscopy in rat cremaster muscle the acute and delayed effects of short exposure to tumor necrosis factor (TNF), interleukin (IL)-1 beta, and IL-6 on basal tone and vascular reactivity of second- to fourth-order arterioles (A2-A4). A 20-min exposure to recombinant human (rh) TNF (0.1-10 ng/ml) induced a significant arteriolar vasodilation, but no significant changes in basal tone were found after exposure to the same doses of IL-1 beta. In contrast, the same exposure to IL-6 (0.1-10 ng/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
30
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 0 publications
3
30
0
Order By: Relevance
“…24 Also, IL-6 causes thromboxane A2-mediated vasoconstriction in rat cremaster muscle arterioles. 25 Although some reports indicate that acute IL-6 infusion does not cause vasoconstriction or Figure 2. A, PRA during baseline conditions and 10 minutes during stress for WT (baseline nϭ9; stress nϭ8) and IL-6 KO (baseline nϭ8; stress nϭ9) mice.…”
Section: Discussionmentioning
confidence: 99%
“…24 Also, IL-6 causes thromboxane A2-mediated vasoconstriction in rat cremaster muscle arterioles. 25 Although some reports indicate that acute IL-6 infusion does not cause vasoconstriction or Figure 2. A, PRA during baseline conditions and 10 minutes during stress for WT (baseline nϭ9; stress nϭ8) and IL-6 KO (baseline nϭ8; stress nϭ9) mice.…”
Section: Discussionmentioning
confidence: 99%
“…Besides vasoconstriction, the accumulation and adherence of leukocytes to the vascular wall seen in sepsis may add to the impaired microcirculation. [27][28][29] Possible mediators of these early microvascular changes include cytokines, which have been reported to increase vascular tone, 18 and endothelial expression of adhesion molecules in early stages of sepsis. 30 In later stages of the disease, the microvascular tone and reactivity, as well as their correlation to cytokine levels, may well differ from the findings in our study.…”
Section: Discussionmentioning
confidence: 99%
“…7,8,14 -17 In sepsis, cytokines are involved in activating vascular and endothelial defense mechanisms that may cause changes in perfusion and vascular resistance in the microcirculation. 18,19 Accordingly, it is possible that cytokine activation is reflected in vascular reactivity. This study was conducted to evaluate the diagnostic use of a vascular reactivity test as compared with that of circulating cytokine levels in infants with suspected sepsis.…”
mentioning
confidence: 99%
“…Several in vivo studies have demonstrated that TNF-α in itself has a vasodilatory effect on second, third, and fourth order arterioles [17]and that TNF-α affects microvascular reactivity to catecholamines [18]. Moreover, TNF-α can regulate several endogenous mediators as being one of the early proinflammatory cytokines, especially in critical conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, TNF-α can regulate several endogenous mediators as being one of the early proinflammatory cytokines, especially in critical conditions. These mediators include potent vasoconstrictive compounds, such as endothelin [19]and interleukin-6 [18]. However, in the present study pretreatment with anti-TNF-α antibody influenced neither the degree of initial surgical trauma-induced vasoconstriction nor the recovery process during the following 24 h. This finding is in line with those of Worrall et al [20], demonstrating that administration of low-dose recombinant TNF-α to healthy rats did not cause local blood flow alterations.…”
Section: Discussionmentioning
confidence: 99%